Soil Remediation: Current Approaches and Emerging Bio-Based Trends - Micaela Santos; Sofia Rebola; Dmitry V. Evtuguin (Soil Systems)
Currently, increasing anthropogenic pressure and overexploitation expose soils to various forms of degradation, including contamination, erosion, and sealing. Soil contamination, primarily caused by industrial processes, agricultural practices (such as the use of pesticides and fertilizers), and improper waste disposal, poses significant risks to human health, biodiversity, and the environment. Common contaminants include heavy metals, mineral oils, petroleum-based hydrocarbons, aromatic hydrocarbons, chlorinated hydrocarbons, and polycyclic aromatic hydrocarbons. Remediation methods for contaminated soils include physical, physicochemical, chemical or biological approaches. This review aims to specify these methods while comparing their effectiveness and applicability in different contamination scenarios. Biochemical methods, particularly phytoremediation, are emphasized for their sustainability, effectiveness, and suitability in arid and semiarid regions. These methods preserve soil quality and promote resource efficiency, waste reduction, and bioenergy production, aligning with sustainability principles and contributing to a circular economy. The integrated phytoremediation–bioenergy approaches reviewed provide sustainable and cost-efficient strategies for environmental decontamination and green development. Special attention is given to the use of lignin in bioremediation. This work contributes to the existing knowledge by outlining priorities for the selection of the most appropriate remediation techniques under diverse environmental conditions, providing a comprehensive overview for future developments.